The globalization of theatre 1870-1930 : the theatrical networks of Maurice E. Bandmann - Balme, Christopher B. (Cambridge studies in modern theatre, 2020)
"When the Anglo-American theatre manager and actor, Maurice E. Bandmann, died of enteric fever at the Colonial Hospital in Gibraltar on 9 March 1922 shortly before his fiftieth birthday, the event was reported across the English-speaking world from Madras to Singapore, and from Cairo to Hong Kong, with many newspapers carrying lengthy obituaries: The Times of India called him 'the pioneer of musical comedy in this part of the world' having 'brought to the East some forty or fifty companies. The Straits Times in Singapore claimed that 'he inaugurated the system that will remain as a monument to his memory in theatrical circles. The Era, London's theatrical trade paper, emphasized 'the fine plays and well-equipped companies he presented (which) became famous in all parts of the world, many stars appearing under his management, and the Bandman Opera Company, with all the latest musical comedy successes, was exceedingly popular everywhere in the East. As these statements indicate, Maurice Bandmann was at the time considered a key figure in what will be called in this book, the globalization of theatre. For over two decades, Bandmann was a household name in the theatre world of the time, a guarantor of quality itinerant theatrical entertainment, especially of musical comedy performed by the legendary Bandmann Opera Company. The Bandmann Circuit, as it was known, extended from Gibraltar to Tokyo and included more than two dozen towns and cities, across the Asian continent as well as occasional forays across to the West Indies and even South America. In terms of sheer reach and territory covered, Bandmann was a global theatrical entrepreneur, who, while certainly concentrating on English-speaking settlements also performed regularly in Japan to Japanese audiences, before Chinese in Shanghai and Peking and numerous cities where audiences were linguistically mixed"--